The fabrication of poly (polyethylene glycol diacrylate) monolithic porous layer open tubular (mono‐PLOT) columns and applications in hydrophilic interaction chromatography and capillary gas chromatography for small molecules. Issue 4 (25th January 2019) - Chang, Feng; Yue, Yunfang; Yang, Zihui; Huang, Si; Liu, Zhihua; Wang, Kunmiao; Peng, Yan; Chen, Yingzhuang; Ma, Ming; Chen, Bo
Abstract: The easy shrinkage and swelling of polymer monolithic column when exposed to mobile phase with different polarity is a problem that cannot be ignored. To overcome this drawback, a convenient aqueous two‐phase polymerization approach was used to prepare poly (polyethylene glycol diacrylate, PEGDA) monolithic porous layer open tubular (mono‐PLOT) columns (150 μm). The poly(PEGDA) mono‐PLOT column with homogeneous polymer porous layer was synthesized successfully. A maximum plate number of 41, 500 plates per meter for allyl thiourea was obtained under a velocity of 1.8 mm/s. Several kinds of polar molecule were separated on the proposed mono‐PLOT column and a typical hydrophilic interaction retention mechanism was observed. High speed separation of benzoic acids was also carried out, baseline separation of five benzoic acids was successfully achieved within 5 min with a 70 cm mono‐PLOT column at 50°C. Furthermore, the resulting PLOT column was also successfully applied to separate standard analytes of three DNA oxidative damage products and RNA‐modified nucleosides and four chlorophenols. At last, the column could separate alcohols, alkanes, and aromatic isomers via GC. It had more than 20, 000 plates per meter for butanol – higher than commercial coatings open tubular columns.